High rate video streaming steganography - Eltahir, M.E.; Kiah, L.M.; Zaidan, B.B.; Zaidan, A.A. (2009)
Steganography is the idea of hiding private or sensitive data or information within something that appears to be nothing out of the ordinary. In this paper we will overview the use of data hiding techniques in digital video as still images. We will describe how we can use the Least Significant Bit insertion (LSB) method on video images or frames, in addition to the usage of the human vision system to increase the size of the data embedded in digital video streaming